Pemikiran Nasiruddin Al-Albani Tentang Hadis Kewajiban Orang Sakit dan Proses Pembimbingannya dalam Kitab Ahkam Al-Janaiz - Nadia Maulida Mahbubiati; Muhid; Khalfiah, Yuliani (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This article will discuss the thoughts of one of the scholars of hadith, Nasiruddin al-Albani, regarding the obligations for someone who is sick and some things that need to be done when the illness has reached its limit. This discussion refers to Nasiruddin al-Albani's work, namely the book Ahkam al-Janaiz wa bida'uha in the chapter ma yajibu ‘ala maridh or obligations for the sick. This article research uses qualitative research methods, especially through library research by taking primary data sources from the book Ahkam al-Janaiz wa bida'uha and secondary data from journal articles, scientific books and related literature. This research also uses the theory of Islamic spiritual guidance to find out the steps taken in Islamic spiritual guidance are the same as the thoughts of a Nasiruddin al-Albani who has the basis of the Prophet's hadith. The results of this study indicate that there are similarities in the process of handling patients using spiritual guidance methods with Nasiruddin al-Albani's thoughts about the obligations for the sick even though it is recommended with the assistance of people who are experts in their fields.